2006
DOI: 10.1051/kmae:2006020
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Astacus Astacus Gonads During the Reproductive Cycle

Abstract: The reproductive cycle of Astacus astacus was described by the external observation of the gonads, recording changes in the gonadosomatic index (GSI) and by the histological analysis of the reproductive organs. A total of 37 males and 13 females of Astacus astacus were collected from the Vukovina gravel pit located at northwest Croatia from May 2003 until January 2004. All crayfish were mature with total body lengths between 7.84 and 13.7 cm and weights between 16 and 125 g. There was a pronounced difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
3
0
4
Order By: Relevance
“…HUNER (1993) found I G -values of Orconectes rusticus (Girard) and Orconectes immunis (Hagen) females of 4% and 5.9%, respectively. LUCIĆ et al (2006) found I G -values of A. astacus males and females of 0.2-1.53% and 0.47-12.3%, respectively. I G -values of 0.4-4.0% towards ovulation were found for P. leniusculus (KOZÁK et al, 2002) and for Cherax albidus (Clark) (McRAE and MITCHELL, 1995;MITCHELL and COLLINS, 1995).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…HUNER (1993) found I G -values of Orconectes rusticus (Girard) and Orconectes immunis (Hagen) females of 4% and 5.9%, respectively. LUCIĆ et al (2006) found I G -values of A. astacus males and females of 0.2-1.53% and 0.47-12.3%, respectively. I G -values of 0.4-4.0% towards ovulation were found for P. leniusculus (KOZÁK et al, 2002) and for Cherax albidus (Clark) (McRAE and MITCHELL, 1995;MITCHELL and COLLINS, 1995).…”
Section: Discussionmentioning
confidence: 85%
“…Then the colour changed from yellow to orange in August and September. From October to spawning in April, the ovary was brown and I G increased, which is different from astacid species (VOGT, 2002;LUCIĆ et al, 2006). Average size of O. limosus oocytes ranged from 1.4 to 1.8 mm which was comparable with 1.8 mm for P. clarkii (ANDO and MAKIOKA, 1998) and 1.2 mm for P. leniusculus (KOZÁK et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…La particular organización de estas células de acuerdo a características morfológicas similares, al interior de los conos de maduración, ha sido previamente reportada por Meeratana & Sobhon (2007) para M. rosenbergii, sugiriendo una maduración sincrónica de los gametos, que progresa a medida que los ovocitos se alejan del centro del ovario. Esta sincronía en la maduración ocurre de igual manera en otros crustáceos (Bell & Ligthner, 1988;Abdu et al, 2000: Elorza & Dupré, 2000Lucić et al, 2006;Vazquez et al, 2008), encontrándose dominancia de ovocitos previtelogénicos o vitelogénicos de acuerdo al estado de desarrollo de la gónada. Por otro lado, la identificación de estados de desarrollo de los ovocitos mediante características histológicas, histoquímicas y patrones de acumulación de vitelo ha sido previamente utilizada por otros autores.…”
Section: Discussionunclassified
“…El cambio de tamaño en los ovocitos se debe principalmente a la rápida incorporación de vitelo proteínico y gotas de lípidos, las cuales aparecen en primera instancia hacia la periferia del citoplasma (Abdu et al, 2000;Lucić et al, 2006;Meeratana & Sobhon, 2007), marcando en algunos casos como en este, la etapa final del estado de previtelogenesis y el inicio de la vitelogénesis temprana. En algunas especies como C. quadricarinatus, donde el ciclo de madurez fue dividido en dos grandes etapas (vitelogénesis primaria y secundaria), la aparición de estas gotas de lípidos señala el final de la vitelogénesis primaria (Abdu et al, 2000).…”
Section: Discussionunclassified
“…Although the structure of the ovarian wall is considered to be important in releasing mature oocytes from the ovary during spawning, it has received little attention. Several studies reported the absence of muscular layers in crustacean ovaries (Adiyodi and Subramoniam, 1983), like in Orconectes nais (Beams and Kessel, 1963), Astacus astacus (Lucić et al, 2006) and A. leptodactylus ( € Uniş and Erkan, 2012). Others reported an ovarian muscle sheath, for example, in Homarus americanus (Talbot, 1981a;Dongfa et al, 2001), Procambarus clarkia (Ando and Makioka, 1998), Procambarus fallax f. virginalis (Vogt et al, 2004), Cambaroides japonicas (Nakata and Goshima, 2004) and Cherax quadricarinatus (Vazquez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%